1978
DOI: 10.1007/bf01477457
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive peptides in experimental renal hypertension

Abstract: 1. Blood pressure is controlled by both integrated neurogenic and humoral vasoactive mechanisms. 2. Both vasopressor (angiotensin and vasopressin) and vasodepressor (bradykinin) hormonal peptides have been identified. 3. In acute experimental renal hypertension in the rat plasma renin, angiotensin and vasopressin have all been shown to be elevated. 4. Associated with this increase in vasopressor hormonal peptides, urinary kallikrein excretion has been demonstrated to be reduced during the development of renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
1984
1984

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Since the early development of renal hypertension is generally believed to be mediated by increased activity of the renin-angiotensin system (liard et al, 1974;Mohring et al, 1975;Carretero and Romero, 1977;Davis, 1977;Johnston et al, 1978), a vasoconstrictor component associated with high circulating levels of angiotension II is one likely candidate for producing the similarity in the overall time waveform of the hindquarters resistance response in protected and unprotected hindquarters. There is also evidence to suggest that sympathetic activity is inappropriately elevated during renal hypertension (Ferrario and McCubbin, 1974;.…”
Section: Possible Mechanisms and Implicationsmentioning
confidence: 99%
“…Since the early development of renal hypertension is generally believed to be mediated by increased activity of the renin-angiotensin system (liard et al, 1974;Mohring et al, 1975;Carretero and Romero, 1977;Davis, 1977;Johnston et al, 1978), a vasoconstrictor component associated with high circulating levels of angiotension II is one likely candidate for producing the similarity in the overall time waveform of the hindquarters resistance response in protected and unprotected hindquarters. There is also evidence to suggest that sympathetic activity is inappropriately elevated during renal hypertension (Ferrario and McCubbin, 1974;.…”
Section: Possible Mechanisms and Implicationsmentioning
confidence: 99%
“…Several studies have demonstrated elevation of plasma AVP in the benign phase of DOC-salt hyperten sion [39], Elevated plasma AVP levels have been re ported in benign renovascular hypertension in rats [39,40] and in dogs [41], spontaneously hypertensive rats (SHR) [39. 42] and in stroke-prone SHR [43].…”
Section: Is Plasma Vasopressin Elevated In Hypertension?mentioning
confidence: 99%